Ultraviolet solar radiation in the tropical central Andes (12.0 degrees S) - Salas, LFS (2017)
Ultraviolet solar irradiance measurements performed in the central Andes, Huancayo, Peru at 1 min intervals between January 2003 and December 2006 were used to analyse daily, monthly, and annual cycles of UV solar irradiance. The measurements were performed using a GUV-511 multi-channel filter radiometer at four wavelengths: 305, 320, 340, and 380 nm. The results indicate that tropical central Andes has among the highest incident ultraviolet solar radiation in the world.